A water-based anti-ultraviolet penetration paint and preparation method thereof

By adding titanium dioxide anti-ultraviolet reagents and polypropylene anti-ultraviolet fibers to the aqueous coating, the problem of aging of water-based paint under ultraviolet irradiation is solved, and the efficient anti-ultraviolet performance and enhanced stability of paint is achieved.

CN118995022BActive Publication Date: 2025-04-04HUIZHOU JUXIN CHEM CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411257625.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2025-04-04
Estimated Expiration
2044-09-09

AI Technical Summary

Technical Problem

Water-based paint is prone to aging under long-term ultraviolet irradiation, affecting the body performance, and the prior art is difficult to effectively improve its anti-ultraviolet penetration performance.

Method used

Titanium dioxide anti-UV reagent and polypropylene anti-UV fiber were added to the aqueous coating system. Titanium dioxide anti-UV reagent was prepared by combining mica and titanium dioxide, and anti-UV sustained-release capsules were attached to the polypropylene fiber.

Benefits of technology

It significantly improves the UV resistance of paint, reduces damage to the body by ultraviolet rays, and improves the impact resistance and stability of paint.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present application relates to a water-based anti-ultraviolet penetration paint and a preparation method thereof, which comprises the following components by mass: 200-260 parts of water-based polyurethane, 30-40 parts of polyester, 60-80 parts of amino resin, 60-80 parts of pigment, 45-54 parts of titanium dioxide anti-ultraviolet agent, 30-40 parts of polypropylene anti-ultraviolet fiber, 4-6g of defoamer, and 6-8g of leveling agent; the titanium dioxide anti-ultraviolet agent comprises mica and titanium dioxide. The present application has the effect of improving the long-term anti-ultraviolet performance of the paint.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of water-based coatings, and in particular to a water-based anti-ultraviolet penetration coating and a preparation method thereof. Background Art

[0002] Water-based paint has excellent non-stickiness and durability. Using water as a solvent can save a lot of resources, eliminate the risk of fire during construction, reduce air pollution, and only use a small amount of low-toxic alcohol ether organic solvents, which improves the working environment conditions. It is widely used in various industries.

[0003] Ultraviolet rays have very high energy, and long-term exposure to ultraviolet rays will accelerate the aging of materials. Water-based paint can be applied to the car body to decorate and protect the car body, but ultraviolet rays have penetrating power, and long-term exposure will also affect the performance of the car body, so it needs to be improved. Summary of the invention

[0004] In order to improve the anti-ultraviolet performance of water-based paint, the present application provides a water-based anti-ultraviolet penetration paint and a preparation method thereof.

[0005] The present application provides a water-based anti-ultraviolet penetration paint and a preparation method thereof using the following technical solutions:

[0006] In the first aspect, the present application provides a water-based anti-ultraviolet penetration paint, which adopts the following technical solution:

[0007] A water-based anti-ultraviolet penetration paint comprises the following components by mass:

[0008] 200-260 parts of waterborne polyurethane, 30-40 parts of polyester, 60-80 parts of amino resin, 60-80 parts of pigment, 45-54 parts of titanium dioxide anti-ultraviolet agent, 30-40 parts of polypropylene anti-ultraviolet fiber, 4-6g of defoaming agent, 6-8g of leveling agent;

[0009] The titanium dioxide anti-ultraviolet agent comprises mica and titanium dioxide.

[0010] By adopting the above technical scheme, adding titanium dioxide anti-ultraviolet agent and polypropylene anti-ultraviolet fiber to the coating system, the overall anti-ultraviolet performance of the paint can be improved; wherein, the titanium dioxide anti-ultraviolet agent is obtained by compounding mica and titanium dioxide, titanium dioxide has good ultraviolet absorption performance, can effectively absorb ultraviolet rays with a wide wavelength range, and at the same time, has high hardness and stable chemical properties; mica also has stable chemical properties, and mica has a layered structure composed of multiple thin layers stacked together, which can cause the incident light to produce multiple reflections and refractions between layers, so mica can be used as a good carrier to load titanium dioxide, thereby synergistically improving the overall anti-ultraviolet performance of the paint.

[0011] Preferably, the titanium dioxide anti-ultraviolet agent is prepared by the following method:

[0012] The mica powder is mixed with deionized water to obtain a mica dispersion, and after heating in a water bath, the pH value is adjusted to be acidic, manganese tetrachloride is mixed with deionized water to obtain a manganese tetrachloride solution, the manganese tetrachloride solution is added to the mica dispersion to obtain a pretreated mica solution, titanium tetrachloride is mixed with anhydrous ethanol to obtain a titanium tetrachloride solution, the titanium tetrachloride solution is added to the pretreated mica solution to react for 1 hour, and the solution is cooled, centrifuged, washed, and dried to obtain a titanium dioxide anti-ultraviolet agent.

[0013] By adopting the above technical solution, titanium dioxide is loaded onto mica sheets, which can effectively improve the dispersion performance of titanium dioxide, reduce the agglomeration of titanium dioxide, increase the surface area and system stability, and thus improve the overall UV resistance of the paint. At the same time, the addition of the crystal form regulator manganese tetrachloride allows titanium dioxide to crystallize and grow on the formed manganese dioxide, inhibiting the photocatalytic activity of titanium dioxide and further improving the UV resistance of the prepared titanium dioxide anti-UV agent.

[0014] Preferably, the mass ratio of mica, titanium dioxide and manganese tetrachloride is (4.4-4.6):1:0.1.

[0015] By adopting the above technical solution, preferably the mass ratio of mica, titanium dioxide and manganese tetrachloride is within the above range, which can further improve the stability of the prepared titanium dioxide anti-ultraviolet agent.

[0016] Preferably, the pH value of the mica dispersion is 1.4-1.8.

[0017] By adopting the above technical solution and controlling the pH value within the above range, the stability of the prepared titanium dioxide anti-ultraviolet agent can be further improved.

[0018] Preferably, the polypropylene anti-ultraviolet fiber comprises silane-modified polypropylene fiber and anti-ultraviolet sustained-release capsule.

[0019] Preferably, the anti-ultraviolet sustained-release capsule is prepared by the following method:

[0020] After isophorone diisocyanate and acetone are mixed, dibutyltin dilaurate is added, 1,4-butanediol, polypropylene glycol and acetone are added by heating in an oil bath, ultrasonic reaction is carried out, and excess acetone is removed by rotary evaporation to obtain a prepolymer;

[0021] A prepolymer, styrene, N-isopropylacrylamide, n-butyl acrylate, silver nitrate and a crosslinking agent are mixed to obtain a mixture, a surfactant is added to the mixture, and an emulsion is obtained after ultrasonic treatment; lignin, ethylene glycol and deionized water are mixed and added to the emulsion, and dibutyltin dilaurate is added to react to obtain anti-ultraviolet sustained-release microcapsules.

[0022] By adopting the above technical scheme, encapsulating the nanosilver particles in microcapsules can delay the release of the nanosilver particles, thereby achieving long-term anti-ultraviolet performance. At the same time, the aromatic rings, double bonds and hydroxyl groups in the molecular structure of lignin can absorb ultraviolet light. Using lignin as the raw material of the microcapsule can further improve the overall anti-ultraviolet performance of the paint system. After the profile is slowly released, the anti-ultraviolet performance of the paint can also be improved. Polypropylene fiber has good mechanical properties. After being dispersed in the paint, it can improve the overall impact resistance of the paint. At the same time, the anti-ultraviolet microcapsules are attached to the surface of the polypropylene fiber. The two can jointly improve the anti-ultraviolet performance of the paint after compounding.

[0023] Preferably, the mass ratio of the prepolymer, silver nitrate and lignin is 1:1.25:(0.08-0.12).

[0024] By adopting the above technical solution, preferably the mass ratio of the prepolymer, silver nitrate and lignin is within the above range, which can effectively improve the stability of the prepared anti-ultraviolet sustained-release microcapsules.

[0025] Preferably, the silane-modified polypropylene fiber is prepared by the following method:

[0026] The γ-aminopropyltriethoxysilane is mixed with deionized water to obtain a silane coupling agent, and the polypropylene fiber is immersed in the silane coupling agent, ultrasonically dispersed, allowed to stand, filtered, and then dried to obtain the silane-modified propylene fiber.

[0027] By adopting the above technical solution and using a silane coupling agent to modify the polypropylene fiber, on the one hand, the dispersion performance of the polypropylene fiber in the system can be improved, thereby improving the stability of the coating system; on the other hand, it is beneficial to the bonding stability between the anti-ultraviolet sustained-release capsule and the polypropylene fiber.

[0028] Preferably, the pH value is 1.4-1.8.

[0029] In a second aspect, the present application provides a method for preparing a water-based anti-ultraviolet penetration paint, which adopts the following technical scheme:

[0030] A method for preparing a water-based anti-ultraviolet penetration paint comprises the following steps:

[0031] The anti-ultraviolet paint is obtained by mixing waterborne polyurethane, polyester, amino resin, pigment, titanium dioxide anti-ultraviolet agent, polypropylene anti-ultraviolet fiber, defoaming agent and leveling agent, and stirring the mixture sufficiently.

[0032] In summary, the present application includes at least one of the following beneficial technical effects:

[0033] 1. Adding titanium dioxide anti-ultraviolet agent and polypropylene anti-ultraviolet fiber to the coating system can synergistically improve the anti-ultraviolet performance of the paint, thereby effectively reducing the damage of ultraviolet rays to the car body; among them, the titanium dioxide anti-ultraviolet agent is prepared by compounding mica and titanium dioxide. The combination of the two can further synergistically improve the anti-ultraviolet performance of the paint. At the same time, mica and titanium dioxide have good mechanical properties, which can effectively improve the impact resistance and stability of the paint;

[0034] 2. The polypropylene anti-ultraviolet fiber is obtained by combining the polypropylene fiber with the anti-ultraviolet sustained-release capsule. The polypropylene fiber itself has good anti-ultraviolet performance. Combining the anti-ultraviolet sustained-release capsule with the polypropylene can synergistically improve the overall anti-ultraviolet performance of the polypropylene fiber. At the same time, it can also make the anti-ultraviolet sustained-release capsule more stably present in the paint, thereby improving the stability of the anti-ultraviolet sustained-release capsule;

[0035] 3. After being treated with silane coupling agent, polypropylene fiber can be more evenly dispersed in the paint system, thereby improving the overall dispersion performance of polypropylene anti-UV fiber. DETAILED DESCRIPTION

[0036] The present application is further described in detail below with reference to the embodiments:

[0037] Description of raw materials: The cross-linking agent is divinylbenzene (CAS No.: 1321-74-0), n-hexadecane (CAS No.: 544-76-3), and azobisisobutyronitrile (CAS No.: 78-67-1) mixed in a mass ratio of 1:1:1; the defoaming agent is polyether modified silicone oil; and the leveling agent is polydimethylsiloxane (CAS No.: 9016-00-6).

[0038] Example 1

[0039] Preparation of titanium dioxide anti-UV reagent:

[0040] 80 g of mica powder was mixed with 500 g of deionized water to obtain a mica dispersion, which was heated to 70° C. in a water bath at a speed of 300 rpm, and hydrochloric acid was added to make the pH value of the mica dispersion 1.4. 1.82 g of manganese tetrachloride was mixed with 50 g of deionized water to obtain a manganese tetrachloride solution, and the manganese tetrachloride solution was added to the mica dispersion, and sodium hydroxide was added to keep the pH value of the mica dispersion constant until all the manganese tetrachloride solution was added to obtain a pretreated mica solution. 18.18 g of titanium tetrachloride was added. (CAS No.: 7550-45-0) was mixed with 50g of anhydrous ethanol to obtain a titanium tetrachloride solution, and the titanium tetrachloride solution was added to the pretreated mica solution while maintaining the temperature and pH value very constant until all the titanium tetrachloride solution was added, and the system concentration and pH value continued to react for 1h, and then the system was cooled to 25°C, centrifuged and washed with deionized water to neutrality, dried in an oven at 100°C for 12h, and then transferred to a muffle furnace and calcined at 500°C for 2h to obtain a titanium dioxide anti-UV agent.

[0041] Preparation of polypropylene UV-resistant fiber:

[0042] After mixing 48 g of isophorone diisocyanate (CAS No.: 4098-71-9) with 100 g of acetone, 0.3 g of dibutyltin dilaurate (CAS No.: 77-58-7) was added, the oil bath was heated to 70°C, and then 2.25 g of 1,4-butanediol (CAS No.: 110-63-4), 50 g of polypropylene glycol (PPG-2000) and 100 g of acetone were added. After ultrasonication, the mixture was reacted for 2.5 h, and the excess acetone was removed by rotary evaporation to obtain a prepolymer.

[0043] 21.46g of prepolymer, 25g of styrene, 10g of N-isopropylacrylamide (CAS No.: 2210-25-5), 5g of n-butyl acrylate (CAS No.: 141-32-2), 26.82g of silver nitrate and 0.5g of cross-linking agent are mixed to obtain a mixture, 7.5g of sodium dodecylbenzene sulfonate (CAS No.: 25155-30-0) and 142.5g of deionized water are mixed to obtain a surfactant, the surfactant is added to the mixture, and an emulsion is obtained after ultrasonic treatment. The emulsion is heated to 50°C; 1.72g of lignin (CAS No.: 8068-05-1), 6g of ethylene glycol and 50g of deionized water are mixed and added to the heated emulsion, and 0.6g of dibutyltin dilaurate is added. The reaction is carried out for 12h, the oil bath is heated to 75°C, and the reaction is continued for 8h to obtain anti-ultraviolet sustained-release microcapsules.

[0044] 3 g of γ-aminopropyltriethoxysilane (CAS No.: 919-30-2) was mixed with 500 g of deionized water to obtain a silane coupling agent, 45 g of polypropylene fiber was immersed in the silane coupling agent, ultrasonically dispersed for 15 min, allowed to stand for 4 h, filtered and dried in an oven at 35 ° C for 8 h to obtain silane-modified propylene fiber, the silane-modified propylene fiber prepared above was immersed in an anti-ultraviolet sustained-release capsule, and 200 g of acetone was added, and the temperature was raised to 40 ° C for 6 h after ultrasonic dispersion. After washing and filtering, the product was dried in an oven at 55 ° C for 3 h to obtain polypropylene anti-ultraviolet fiber.

[0045] Preparation of UV-resistant paint:

[0046] 200 g of waterborne polyurethane, 30 g of polyester, 60 g of amino resin, 60 g of pigment, 45 g of titanium dioxide anti-UV agent, 30 g of polypropylene anti-UV fiber, 4 g of defoaming agent, and 6 g of leveling agent were mixed, and stirred at a speed of 1200 rpm for 30 minutes to obtain anti-UV paint.

[0047] Example 2

[0048] Preparation of titanium dioxide anti-UV reagent:

[0049] 80.71 g of mica powder was mixed with 500 g of deionized water to obtain a mica dispersion, which was heated to 70° C. in a water bath at a speed of 300 rpm, and hydrochloric acid was added to adjust the pH value of the mica dispersion to 1.8. 1.75 g of manganese tetrachloride was mixed with 50 g of deionized water to obtain a manganese tetrachloride solution, and the manganese tetrachloride solution was added to the mica dispersion, and sodium hydroxide was added to keep the pH value of the mica dispersion constant until all the manganese tetrachloride solution was added to obtain a pretreated mica solution. 17 .54g of titanium tetrachloride is mixed with 50g of anhydrous ethanol to obtain a titanium tetrachloride solution, and the titanium tetrachloride solution is added to the pretreated mica solution while keeping the temperature and pH very constant until all the titanium tetrachloride solution is added, and the system concentration and pH value continue to react for 1h, then the system is cooled to 25°C, centrifuged and washed with deionized water to neutrality, dried in an oven at 100°C for 12h, and then transferred to a muffle furnace and calcined at 500°C for 2h to obtain a titanium dioxide anti-UV agent.

[0050] Preparation of polypropylene UV-resistant fiber:

[0051] After mixing 48 g of isophorone diisocyanate with 100 g of acetone, 0.3 g of dibutyltin dilaurate was added, the oil bath was heated to 70°C, and then 2.25 g of 1,4-butanediol, 50 g of polypropylene glycol and 100 g of acetone were added. After ultrasonication, the mixture was reacted for 2.5 h, and excess acetone was removed by rotary evaporation to obtain a prepolymer.

[0052] 21.1 g of prepolymer, 25 g of styrene, 10 g of N-isopropylacrylamide, 5 g of n-butyl acrylate, 26.37 g of silver nitrate and 0.5 g of cross-linking agent are mixed to obtain a mixture, 7.5 g of sodium dodecylbenzene sulfonate is mixed with 142.5 g of deionized water to obtain a surfactant, the surfactant is added to the mixture, and an emulsion is obtained after ultrasonic treatment. The emulsion is heated to 50°C; 2.53 g of lignin, 6 g of ethylene glycol and 50 g of deionized water are mixed and added to the heated emulsion, and 0.6 g of dibutyltin dilaurate is added. The reaction is carried out for 12 hours, the oil bath is heated to 75°C, and the reaction is continued for 8 hours to obtain anti-ultraviolet sustained-release microcapsules.

[0053] 5 g of γ-aminopropyltriethoxysilane was mixed with 500 g of deionized water to obtain a silane coupling agent, 45 g of polypropylene fiber was soaked in the silane coupling agent, ultrasonically dispersed for 15 min, allowed to stand for 4 h, filtered and dried in an oven at 35 ° C for 8 h to obtain silane-modified propylene fiber, the prepared silane-modified propylene fiber was soaked in an anti-ultraviolet sustained-release capsule, and 200 g of acetone was added, and the temperature was raised to 40 ° C for 6 h after ultrasonic dispersion. After washing and filtering, the product was dried in an oven at 55 ° C for 3 h to obtain polypropylene anti-ultraviolet fiber.

[0054] Preparation of UV-resistant paint:

[0055] 260 g of waterborne polyurethane, 40 g of polyester, 80 g of amino resin, 80 g of pigment, 54 g of titanium dioxide anti-UV agent, 40 g of polypropylene anti-UV fiber, 6 g of defoaming agent, and 8 g of leveling agent were mixed, and stirred at a speed of 1200 rpm for 30 minutes to obtain anti-UV paint.

[0056] Example 3

[0057] Preparation of titanium dioxide anti-UV reagent:

[0058] 80.35 g of mica powder was mixed with 500 g of deionized water to obtain a mica dispersion, and the mixture was heated to 70° C. in a water bath at a speed of 300 rpm, and hydrochloric acid was added to adjust the pH value of the mica dispersion to 1.6. 1.79 g of manganese tetrachloride was mixed with 50 g of deionized water to obtain a manganese tetrachloride solution, and the manganese tetrachloride solution was added to the mica dispersion, and sodium hydroxide was added to keep the pH value of the mica dispersion constant until all the manganese tetrachloride solution was added to obtain a pretreated mica solution. 17 .86g of titanium tetrachloride was mixed with 50g of anhydrous ethanol to obtain a titanium tetrachloride solution, and the titanium tetrachloride solution was added to the pretreated mica solution while maintaining the temperature and pH value very constant until all the titanium tetrachloride solution was added, and the system concentration and pH value continued to react for 1h, and then the system was cooled to 25°C, centrifuged and washed with deionized water to neutrality, dried in an oven at 100°C for 12h, and then transferred to a muffle furnace and calcined at 500°C for 2h to obtain a titanium dioxide anti-UV agent.

[0059] Preparation of polypropylene UV-resistant fiber:

[0060] After mixing 48 g of isophorone diisocyanate with 100 g of acetone, 0.3 g of dibutyltin dilaurate was added, the oil bath was heated to 70°C, and then 2.25 g of 1,4-butanediol, 50 g of polypropylene glycol and 100 g of acetone were added. After ultrasonication, the mixture was reacted for 2.5 h, and excess acetone was removed by rotary evaporation to obtain a prepolymer.

[0061] 21.28 g of prepolymer, 25 g of styrene, 10 g of N-isopropylacrylamide, 5 g of n-butyl acrylate, 26.6 g of silver nitrate and 0.5 g of cross-linking agent are mixed to obtain a mixture, 7.5 g of sodium dodecylbenzene sulfonate is mixed with 142.5 g of deionized water to obtain a surfactant, the surfactant is added to the mixture, and an emulsion is obtained after ultrasonic treatment. The emulsion is heated to 50° C.; 2.12 g of lignin, 6 g of ethylene glycol and 50 g of deionized water are mixed and added to the heated emulsion, and 0.6 g of dibutyltin dilaurate is added. The reaction is carried out for 12 hours, the oil bath is heated to 75° C., and the reaction is continued for 8 hours to obtain anti-ultraviolet sustained-release microcapsules.

[0062] 4 g of γ-aminopropyltriethoxysilane was mixed with 500 g of deionized water to obtain a silane coupling agent, 45 g of polypropylene fiber was immersed in the silane coupling agent, ultrasonically dispersed for 15 min, allowed to stand for 4 h, filtered and dried in an oven at 35 ° C for 8 h to obtain silane-modified propylene fiber, the silane-modified propylene fiber prepared above was immersed in an anti-ultraviolet sustained-release capsule, and 200 g of acetone was added, and the temperature was raised to 40 ° C for 6 h after ultrasonic dispersion. After washing and filtering, the product was dried in an oven at 55 ° C for 3 h to obtain polypropylene anti-ultraviolet fiber.

[0063] Preparation of UV-resistant paint:

[0064] 230 g of waterborne polyurethane, 35 g of polyester, 70 g of amino resin, 70 g of pigment, 50 g of titanium dioxide anti-UV agent, 35 g of polypropylene anti-UV fiber, 5 g of defoaming agent, and 7 g of leveling agent were mixed, and stirred at a speed of 1200 rpm for 30 min to obtain anti-UV paint.

[0065] Example 4

[0066] Example 4 is based on Example 3. The difference between Example 4 and Example 3 is that when preparing the titanium dioxide anti-ultraviolet agent in Example 4, 78.43 g of mica, 19.61 g of titanium tetrachloride, and 1.96 g of manganese tetrachloride are weighed.

[0067] Example 5

[0068] Example 5 is based on Example 3. The difference between Example 5 and Example 3 is that when preparing the titanium dioxide anti-ultraviolet agent in Example 5, 81.97 g of mica, 16.39 g of titanium tetrachloride, and 1.64 g of manganese tetrachloride are weighed.

[0069] Example 6

[0070] Example 6 is based on Example 3. The difference between Example 6 and Example 3 is that hydrochloric acid is used in Example 6 to adjust the pH value of the mica dispersion to 1.2.

[0071] Example 7

[0072] Example 7 is based on Example 3. The difference between Example 7 and Example 3 is that hydrochloric acid is used to adjust the pH value of the mica dispersion to 2 in Example 7.

[0073] Example 8

[0074] Example 8 is based on Example 3. The difference between Example 8 and Example 3 is that in Example 8, when preparing the anti-ultraviolet sustained-release microcapsules, 21.83 g of prepolymer, 27.29 g of silver nitrate and 0.88 g of lignin are used.

[0075] Example 9

[0076] Example 9 is based on Example 3. The difference between Example 9 and Example 3 is that in Example 9, when preparing the anti-ultraviolet sustained-release microcapsules, 20.75 g of prepolymer, 25.93 g of silver nitrate and 3.32 g of lignin are used.

[0077] Example 10

[0078] Example 10 is based on Example 3. The difference between Example 10 and Example 3 is that in Example 10, γ-aminopropyltriethoxysilane is not used to treat the polypropylene fiber.

[0079] Embodiment 11

[0080] Example 11 is based on Example 3. The difference between Example 11 and Example 3 is that in Example 3, the anti-ultraviolet sustained-release microcapsules are replaced by nano silver ions when using polypropylene anti-ultraviolet fibers.

[0081] Example 12

[0082] Example 12 is based on Example 3. The difference between Example 12 and Example 3 is that the polypropylene anti-ultraviolet fiber in Example 12 is ordinary polypropylene fiber.

[0083] Example 13

[0084] Example 13 is based on Example 3. The difference between Example 13 and Example 3 is that the titanium dioxide anti-ultraviolet agent in Example 13 is prepared by physically mixing titanium dioxide and mica.

[0085] Comparative Example 1

[0086] Comparative Example 1 is based on Example 3. The difference between Comparative Example 1 and Example 3 is that in Comparative Example 1, the titanium dioxide anti-ultraviolet agent is ordinary nano titanium dioxide particles.

[0087] Performance testing

[0088] The samples of Examples 1-13 and Comparative Example 1 were sampled and the following performance tests were performed:

[0089] (1) UV transmittance performance test

[0090] The UV transmittance performance test was carried out on the samples. Each sample was tested three times, the average value was taken, and the test results were filled in Table 1.

[0091] (2) UV aging performance test

[0092] The UV aging performance test of the samples was carried out according to GB / T 31881-2015 Test Method for Ultraviolet Accelerated Aging of Automotive Non-metallic Parts and Materials. UVA-340 lamps were used with a radiation of 0.89±0.02W / m 2 , wavelength is 340nm, condense at a blackboard temperature of 50℃±3℃ for 4h, and irradiate with ultraviolet light at a blackboard temperature of 70℃±3℃ for 8h and 72h respectively, then observe the samples, test each sample 3 times, and fill in the test results in Table 1.

[0093] (3) Impact resistance test

[0094] According to GB 1732-1993 Determination of impact resistance of paint film, the impact resistance of the samples was tested. Each sample was tested three times, the average value was taken, and the test results were filled in Table 1.

[0095] Table 1 Performance test results of samples of Examples 1-13 and Comparative Example 1

[0096]

[0097] Data analysis

[0098] From Table 1, it can be seen that the UV transmittance of Examples 1-3 of the present application is 4% or less, indicating that the paint prepared in the present application has good UV resistance; after UV aging, no cracking, blistering or peeling occurred in Examples 1-3, and the glossiness was above 90%, indicating that the paint prepared in the present application has good long-term UV resistance; from Table 1, it can be seen that Examples 1-3 have good impact resistance, and it can be seen that the paint prepared in the present application has good impact resistance.

[0099] In Examples 4 and 5, when preparing titanium dioxide anti-ultraviolet agents, the mass ratios of mica, titanium tetrachloride and manganese tetrachloride are not within the range specified in the present application. When the mica content is too high, the hydrolysis products of titanium tetrachloride and manganese tetrachloride are difficult to quickly transfer to the mica surface, making it difficult to form a uniform coating on the mica surface, and the mica loading is low. When the mica content is too low, the excessive manganese dioxide content formed is too saturated, and the excess manganese dioxide agglomerates. At the same time, excessive titanium dioxide content will also reduce the uniformity of titanium dioxide on the mica surface, thereby reducing the uniformity of the titanium dioxide anti-ultraviolet agent and reducing the stability of the paint. Therefore, the various performances of Examples 4 and 5 are all reduced.

[0100] In Example 6 and Example 7, when preparing the titanium dioxide anti-ultraviolet agent, the pH value of the mica dispersion is not within the range specified in the present application. When the pH value of the mica dispersion is too low, the diameter of the titanium dioxide loaded on the mica surface is too small, and the titanium dioxide coating is too dense, thereby reducing the overall dispersion performance of the mica, affecting the performance of the titanium dioxide anti-ultraviolet agent; when the pH value of the mica dispersion is too high, the diameter of the formed nano-titanium dioxide particles is too large and the particle size uniformity is reduced, and the dispersion uniformity and density on the mica surface are reduced, affecting the performance of the titanium dioxide anti-ultraviolet agent, so the various performances of Example 6 and Example 7 are reduced.

[0101] When preparing the anti-ultraviolet sustained-release capsules in Examples 8 and 9, the mass ratios of the prepolymer, silver nitrate and lignin are not within the range specified in the present application. When the lignin content is too low, it is difficult to form a uniform shell on the outer wall of the prepolymer, which reduces the coating effect of the lignin, thereby affecting the anti-ultraviolet performance of the anti-ultraviolet sustained-release capsules. When the lignin content is too high, the lignin shell formed outside the prepolymer will be too thick, affecting the release of silver ions in the core material, thereby affecting the long-term anti-ultraviolet performance of the anti-ultraviolet sustained-release capsules.

[0102] The polypropylene fiber in Example 10 was not treated with γ-aminopropyltriethoxysilane, so the binding effect between the anti-UV sustained-release capsules and the polypropylene fiber was reduced, and some anti-UV sustained-release capsules were free in the system. At the same time, the dispersion performance of the polypropylene fiber was also reduced, affecting the overall stability of the paint. Therefore, the performance of Example 10 was reduced.

[0103] In Example 11, the anti-ultraviolet sustained-release capsules were replaced with nanosilver particles. The binding effect between ordinary nanosilver particles and polypropylene fibers was not high. Some nanosilver particles were free in the paint system and agglomerated, affecting the overall stability of the system. At the same time, the nanosilver particles were not coated with microcapsules. After a long time, the anti-ultraviolet performance of the nanosilver particles decreased. Therefore, all performances in Example 11 decreased.

[0104] In Example 12, the polypropylene anti-ultraviolet fiber is only ordinary polypropylene fiber. The anti-ultraviolet performance of the polypropylene fiber without anti-ultraviolet sustained-release capsule is reduced, and it is difficult to form a stable network structure. At the same time, the impact resistance is affected, and it is difficult to achieve long-term anti-ultraviolet performance.

[0105] The titanium dioxide anti-UV agent in Example 13 only physically mixes titanium dioxide particles with mica. The binding performance between the titanium dioxide anti-UV agents only through physical mixing is reduced, and it is difficult to enhance the shielding effect against ultraviolet rays. In addition, the crystal form of titanium dioxide is difficult to change, and agglomeration occurs in the system, affecting the overall stability and mechanical properties of the system. Therefore, the performance of Example 13 is reduced.

[0106] The titanium dioxide anti-ultraviolet agent in Comparative Example 1 is only titanium dioxide particles, which will agglomerate in the system, and the lack of mica will affect the overall mechanical properties and stability of the paint, so all performances in Comparative Example 1 are reduced.

[0107] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Through the above description, relevant staff can make various changes and modifications without deviating from the technical idea of ​​the present application. The technical scope of the present application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A water-based anti-ultraviolet penetration paint, characterized in that: The composition comprises the following components in parts by weight: Waterborne polyurethane 200-260g, polyester 30-40g, amino resin 60-80g, pigment 60-80g, titanium dioxide anti-UV agent 45-54g, polypropylene anti-UV fiber 30-40g, defoamer 4-6g, leveling agent 6-8g; The titanium dioxide anti-ultraviolet agent comprises mica and titanium dioxide; The polypropylene anti-ultraviolet fiber comprises silane-modified polypropylene fiber and anti-ultraviolet sustained-release capsule; The anti-ultraviolet sustained-release capsule is prepared by the following method: After isophorone diisocyanate and acetone are mixed, dibutyltin dilaurate is added, 1,4-butanediol, polypropylene glycol and acetone are added by heating in an oil bath, ultrasonic reaction is carried out, and excess acetone is removed by rotary evaporation to obtain a prepolymer; A prepolymer, styrene, N-isopropylacrylamide, n-butyl acrylate, silver nitrate and a crosslinking agent are mixed to obtain a mixture, a surfactant is added to the mixture, and an emulsion is obtained after ultrasonic treatment; lignin, ethylene glycol and deionized water are mixed and added to the emulsion, and dibutyltin dilaurate is added to react to obtain anti-ultraviolet sustained-release microcapsules; The mass ratio of the prepolymer, silver nitrate and lignin is 1:1.25:(0.08-0.12).

2. The water-based anti-ultraviolet penetration paint according to claim 1, characterized in that: The titanium dioxide anti-ultraviolet agent is prepared by the following method: The mica powder is mixed with deionized water to obtain a mica dispersion, and after heating in a water bath, the pH value is adjusted to be acidic, manganese tetrachloride is mixed with deionized water to obtain a manganese tetrachloride solution, the manganese tetrachloride solution is added to the mica dispersion to obtain a pretreated mica solution, titanium tetrachloride is mixed with anhydrous ethanol to obtain a titanium tetrachloride solution, the titanium tetrachloride solution is added to the pretreated mica solution to react for 1 hour, and the solution is cooled, centrifuged, washed, and dried to obtain a titanium dioxide anti-ultraviolet agent.

3. The water-based anti-ultraviolet penetration paint according to claim 2, characterized in that: The pH value of the mica dispersion is 1.4-1.

8.

4. The water-based anti-ultraviolet penetration paint according to claim 1, characterized in that: The silane-modified polypropylene fiber is prepared by the following method: The γ-aminopropyltriethoxysilane is mixed with deionized water to obtain a silane coupling agent, the polypropylene fiber is immersed in the silane coupling agent, ultrasonically dispersed, allowed to stand, filtered, and then dried to obtain the silane-modified polypropylene fiber.

5. A method for preparing the anti-ultraviolet penetration paint according to claim 1, characterized in that: The steps include: The waterborne polyurethane, polyester, amino resin, pigment, titanium dioxide anti-ultraviolet agent, polypropylene anti-ultraviolet fiber, defoaming agent and leveling agent are mixed and fully stirred to obtain anti-ultraviolet paint.

Citation Information

Patent Citations

  • High-quality fogging surface treating agent for leather raw materials for leather product production

    CN107723393A

  • Anti-aging sealed plastic box and preparation method thereof

    CN118126453A